If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(r + 2)(r + 2) = 72 Reorder the terms: 2(2 + r)(r + 2) = 72 Reorder the terms: 2(2 + r)(2 + r) = 72 Multiply (2 + r) * (2 + r) 2(2(2 + r) + r(2 + r)) = 72 2((2 * 2 + r * 2) + r(2 + r)) = 72 2((4 + 2r) + r(2 + r)) = 72 2(4 + 2r + (2 * r + r * r)) = 72 2(4 + 2r + (2r + r2)) = 72 Combine like terms: 2r + 2r = 4r 2(4 + 4r + r2) = 72 (4 * 2 + 4r * 2 + r2 * 2) = 72 (8 + 8r + 2r2) = 72 Solving 8 + 8r + 2r2 = 72 Solving for variable 'r'. Reorder the terms: 8 + -72 + 8r + 2r2 = 72 + -72 Combine like terms: 8 + -72 = -64 -64 + 8r + 2r2 = 72 + -72 Combine like terms: 72 + -72 = 0 -64 + 8r + 2r2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-32 + 4r + r2) = 0 Factor a trinomial. 2((-8 + -1r)(4 + -1r)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-8 + -1r)' equal to zero and attempt to solve: Simplifying -8 + -1r = 0 Solving -8 + -1r = 0 Move all terms containing r to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1r = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1r = 0 + 8 -1r = 0 + 8 Combine like terms: 0 + 8 = 8 -1r = 8 Divide each side by '-1'. r = -8 Simplifying r = -8Subproblem 2
Set the factor '(4 + -1r)' equal to zero and attempt to solve: Simplifying 4 + -1r = 0 Solving 4 + -1r = 0 Move all terms containing r to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1r = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1r = 0 + -4 -1r = 0 + -4 Combine like terms: 0 + -4 = -4 -1r = -4 Divide each side by '-1'. r = 4 Simplifying r = 4Solution
r = {-8, 4}
| 20+14y=14y | | X^3-2x-25x+50=0 | | 5/7+6/7x=25/28+5/4x+7/4 | | 3(y-4)=4 | | 8c+16/3=c-8 | | x-4/3=1/2 | | (x+2)(x-3)+x=4-(1-x)(3-x)(3-x)+2(x+1)2 | | x+2=4x | | 6w-4=4w | | 9x+5=6+2x | | 2x+2y=x+3y | | 3x^2=12x-12 | | 3x^2+1=5x^2+4x | | n/0.28=0.6/0.42 | | 2k^2-9k=-9 | | 1/2x=-1/2x+4 | | .30x+(.20)(12-x)=(.25)(12) | | 9/15=m/17 | | 11x-y=16 | | w*l=48 | | 8(x+3)=6(2x) | | 7x-2(4x-5)=15+21x | | wxl=48 | | 1233x=123 | | -x+y=-8 | | w(l)=48 | | 4x+18=3+9x | | 2,5/10=9/x | | -y+10=-3y-4 | | 11,5/10x | | 3/4x-6=11-y | | x(6)=3(15) |